Avaliação sorológica de vacinas comerciais polivalentes contra a enterotoxemia em caprinos - Veschi, Josir Laine Aparecida (2012)
We evaluated the serological response of five commercial polyvalent vaccines containing epsilon toxoid of Clostridium perfringens type D. For this, 84 young goats were randomly divided into six groups, with 14 animals in each group. The goats in the Control Group were not vaccinated, while goats of Groups 1 to 5 received two vaccine shots four weeks apart. The first shot was administered when the goats were 45 (± 3) days old and the second at 75 (± 3). Blood samples for serological tests were collected on days zero, and 30, 60, 90, 120 and 150 after the start of the experiment. The Indirect ELISA technique was used to quantify the epsilon antitoxin antibodies for Clostridium perfringens type D. In general, the mean serum antibody titers of goats on day 60 increased as a response to the two vaccine shots received on days zero and 30. The largest number of animals considered protected was also detected on day 60, in response to the two vaccine shots. Only five animals from Group 1 and one goat from Group 3 displayed antibody titers that are considered protective up to 150 days after vaccination. Based on these results, we concluded that the evaluated vaccines showed poor ability of stimulate a protective immune response in the assessed goats.